Changes over time in mental well-being, fruit and vegetable consumption and physical activity in a community-based lifestyle intervention: a before and after study. (May 2017) - Johnson, R.; Robertson, W.; Towey, M.; Stewart-Brown, S.; Clarke, A.
Abstract: Objectives: There is a theoretical basis for believing that healthy lifestyle interventions can improve mental well-being and evidence to show that mental well-being is protective of future health. This study contributes to the evidence base by examining changes in mental well-being associated with the One Body One Life (OBOL) healthy lifestyle programme in a community setting in the West Midlands. Study design: Quantitative, before and after the evaluation. Methods: We conducted a before and after study of the lifestyle intervention 'OBOL', a multi component intervention that includes exercise and healthy eating education. Mental well-being was measured with the Warwick–Edinburgh Mental Well-being Scale. Physical activity and fruit and vegetable consumption were self-reported. Measures were collected before and after the 12-week intervention and three months post completion. Non-parametric tests were used to assess differences between groups, and linear mixed models were used to assess change over time. Results: Four hundred and eighty-one (81% of attendees) adult participants completed a valid Warwick–Edinburgh Mental Well-being Scale before starting OBOL; of whom, 63.8% completed the Warwick–Edinburgh Mental Well-being Scale immediately post intervention and 25.2% at three months. Mental well-being levels increased significantly ( P  < 0.001) over the course of the intervention and were sustained at the three-month follow-up (baseline median Warwick–Edinburgh Mental Well-being Scale score = 48 [interquartile range 41–55], completion = 53 [interquartile range 46–57], 3-month follow-up = 52 [interquartile range 46–56]). Change in mental well-being was clinically significant after accounting for age and gender. Changes in both fruit and vegetable consumption and physical activity appeared to explain some but not all of the variation in mental well-being. Conclusion: We found significant improvements in mental well-being among participants directly after the intervention which were sustained at the three-month follow-up. These findings contribute to a growing body of knowledge on the contribution of lifestyle interventions to promoting and sustaining mental well-being. Highlights: Mental well-being levels increased significantly over the course of the One Body One Life intervention and were sustained at the three-month follow-up. Changes in fruit and vegetable consumption, and physical activity appeared to explain some but not all of the variations in mental well-being. Fruit and vegetable consumption may have a role to play in the improvement of mental well-being, in conjunction with physical activity. These findings contribute to a growing body of knowledge on the contribution of lifestyle interventions to promoting and sustaining mental well-being.